2007
DOI: 10.1539/sangyoeisei.49.103
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Health Conditions on Work Performance in Japanese Companies

Abstract: Chronic disease has a significant impact on workers' productivity. The aim of this study was to determine the prevalence of chronic health conditions, the work impairment score, and the total lost working hours absent at companies in Japan. Eligible participants were all 544 workers of 4 manufacturing companies in the Kanto area. The Stanford Presenteeism Scale that was developed by Merck & Co., Inc and Stanford University was translated into Japanese and was given to the workers at a periodic health examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…The SPS 11) and WFun 13) were measured in the survey at T1. The SPS was translated into Japanese and already validated 35) . The SPS score ranged from 10 to 50, with higher scores being indicative of greater presenteeism.…”
Section: Other Presenteeism Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPS 11) and WFun 13) were measured in the survey at T1. The SPS was translated into Japanese and already validated 35) . The SPS score ranged from 10 to 50, with higher scores being indicative of greater presenteeism.…”
Section: Other Presenteeism Scalesmentioning
confidence: 99%
“…The SPS score ranged from 10 to 50, with higher scores being indicative of greater presenteeism. The score was calculated only when a respondent endorsed any of 13 chronic conditions 35) .…”
Section: Other Presenteeism Scalesmentioning
confidence: 99%
“…This was 2.4 times higher than in 1996. Employers must pay particular attention to depression in employees because it has a negative impact on productivity [3, 4]. Major depression is a multifactorial disorder [5], and examining risk factors can help employers and managers take measures toward the prevention of depression among workers.…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that in terms of total working hours lost because of primary chronic health conditions, depression was among the top three conditions (Wada et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…A prospective cohort study of workers with mental illnesses among paediatric residents revealed that those who were depressed made 6.2-fold more medication errors per resident per month than residents who were not depressed (Fahrenkopf et al 2008). Another study revealed that in terms of total working hours lost because of primary chronic health conditions, depression was among the top three conditions (Wada et al 2007).…”
Section: Introductionmentioning
confidence: 99%